Congo: The Epic History of a People - Reybrouck, David van (Harper Collins, 2014)
Epic yet eminently readable, penetrating and profoundly moving, ‘Congo’ traces the fate of one of the world's most devastated countries, second only to war-torn Somalia: the Democratic Republic of Congo. With a span of several hundred years and an enormous cast of characters, ‘Congo’ chronicles the most dramatic episodes of the nation’s history, the people and events that have determined Congo’s development – from the slave trade to the ivory and rubber booms; from the arrival of Henry Morton Stanley and his meeting with Dr Livingstone to the brutal regime of Belgium’s King Leopold II; from the struggle for independence to Mobutu's exploitative rule; and from Muhammad Ali and George Foreman’s world famous ‘Rumble in the Jungle’ to the civil war over natural resources that began in 1996 and still rages today. David Van Reybrouck interweaves his own family's history with the voices of a diverse range of individuals – charismatic dictators, feuding warlords, child-soldiers, elderly, female smugglers, and many in the African diaspora of Europe and China – to offer a deeply humane approach to political history, focusing squarely on the Congolese perspective in an attempt to return a nation's history to its people.
Keywords: History / Africa / General; History / General